Fulminant type 1 diabetes mellitus in pregnancy - Li,Chun-Yu (2020)
Fulminant type 1 diabetes mellitus (FT1DM) has received clinical attention for its low incidence and poor prognosis. Currently, few cases of FT1DM are associated with pregnancy in clinical practice, but it poses a great threat to the life of mothers and infants. Here, we present two cases of FT1DM in pregnancy. In Case 1, the patient was a 26-year-old woman who was admitted to the hospital with reduced fetal movement. She was diagnosed with FT1DM and delivered a dead female fetus. Lispro and lantus were administered to control blood glucose, and lipoic acid for antioxidant therapy. In Case 2, the patient was a 28-year-old woman who developed nausea, vomiting, diarrhea, and polydipsia, which later proved to be FT1DM. An abortion was induced and blood glucose levels were controlled using an insulin pump. All physicians should be aware of this disease in order to provide prompt diagnosis and emergency treatment, thus improving maternal prognosis. We suggest that plasma glucose/hemoglobin A1C ratio be adopted as a new clinical parameter in predicting FT1DM.